Submucosal lipoma of the sigmoid colon as a rare cause of mucoid diarrhea: a case report - Dassanayake, S. U. B. (J Med Case Rep, 2016)
BACKGROUND: Symptomatic presentations of colonic lipomas are very rare in clinical practice, and may mimic colonic malignancy. The likelihood of presenting symptoms has been shown to depend on the size of the lesion. CASE PRESENTATION: We describe the case of a 72-year-old Sinhalese man presenting with worsening mucoid diarrhea who was subsequently diagnosed to have a lipoma of the sigmoid colon. His disease was successfully managed with endoscopic resection. CONCLUSION: Confidently establishing the rare diagnosis of a colonic lipoma usually requires a combination of endoscopic, radiological, and histological evaluation, and is therefore very challenging. With the advancement of endoscopic procedures, endoscopic resection is widely practiced as the definitive management of these cases.